The Effect of the addition of Durian (Durio Zibethinus Murr) Flesh on Gayo Arabica Wine Coffee Characteristics - Wanda Krisna Dinata; Novizar Nazir; Gunarif Taib (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2021)
The effect of durian flesh on the characteristics of Gayo Arabica wine coffee quality by fermentation methods has been investigated. This study aims to determine the effect of giving durian flesh to the characteristics of the Arabica Gayo wine coffee and to determine the optimum addition amount of durian flesh. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. Data analysis using ANOVA was then continued with Duncan's New Multiple Range test (DNMRT) at a significance level of 5%. The treatments were: the addition of durian flesh 0, 25, 50, 75, and 100 g to 1000 g of a coffee cherry. Based on the sensory test, the highest score was obtained by adding 0 g of durian flesh to 1000 g coffee cherry (Score: 76.5) which was followed by the addition of 75 g of durian pulp to 1000 g coffee cherry (score: 72.75). The results showed that the addition of durian pulp had a significant effect on the ash content and caffeine content but did not significantly affect the water content. It can be seen that the addition of durian flesh for fermentation for 30 days is not suitable, because it can cause over-fermentation Over fermentation can cause a decrease in the sensory score of the arabica wine coffee.